ASSOCIATION BETWEEN ACADEMIC EXPECTATION, ACADEMIC SELF PERCEPTION WITH ACADEMIC STRESS AMONG UNDERGRADUATE STUDENTS - Kaphle, Maheshor; Karki, Rajesh; Regmi, Nirmala; Neupane, Awijit; Khanal, Sudip; Aryal, Dipsikha; Ghimire, Amrita (Journal of Chitwan Medical College, 2024)
Background: Academic factors such as examination time, parent’s and peer’s pressure worried of getting a job after passing out, and unrealistic expectations of parents and teachers would be connected with academic stress. So, this study was designed to find out the association between academic expectation and academic stress among undergraduate public health students in Kathmandu Nepal. Methods: A cross-sectional study was conducted from 1st March 2022 to 1st May 2023 by including 305 students studying Bachelor of Public Health in Kathmandu Valley. The colleges were selected through simple random sampling and data was collected through a self-administered questionnaire from final-year students. The Scale for Assessing Academic Stress (SAAS) was used to measure the perception of academic stress and academic expectations were measured through questionnaire. Association between academic expectation and academic stress was measure by a chi-square test and the p-value of 0.05 was considered a significant level. Results: The prevalence of high academic stress was 83(27.2%). Most of the students were stressed during examination time, nearly one-third of students believed competition with peers was quite intense and their teachers were critical of their academic performance. The association between academic expectation, and academic stress were statistically significant. Conclusions: Academic expectation was found to be associated with academic stress. Few of the students were found to have high academic stress which may demand scheduled academic counselling, motivation, and guidance to reduce the academic stress. Further research may be required to establish the effect size of academic expectations on academic stress.